Impact of inflammation on recurrent gastroduodenal ulcer bleeding - Oksana N Sulaeva; P. G. Kondratenko; V. Yu. Dely; S. O. Zharikov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of investigation. To analyze the role of inflammatory response in determination of the outcome of acute gastroduodenal ulcer bleeding. Material and methods. All patients, enrolled in the study were divided into two groups, according to the bleeding outcome. The 1st group included patients with sustained hemostasis, the 2nd - with recurrent bleeding within 3 days after admission to the hospital. Severity and pattern of neutrophilic and macrophageal infiltration at biopsy specimens was assessed by immunohistochemistry (CD68). Effect of leukocytes on platelet aggregation induced by collagen and adenosinediphosphate was estimated in vitro. Results. Development of ulcer bleeding was followed by acute inflammatory reaction, severe local information and destruction of marginal ulcer zones. Prognostic factors, increasing the risk of recurrent bleeding were established: elevation of peripheral blood fibrinogen level (p=0,049), endoscopic signs of ongoing bleeding (p=0,005), increase in neutrophil (p=0,015) and macrophage count in marginal ulcer zones (p=0,001). Increase in macrophage count had positive correlation to sever ity of edema, neutrophilic infiltration and progressing alteration of the marginal ulcer zones. Inhibiting effect of leukocytes on collagen-induced platelet aggregation (p=0,008) that can limit thrombogenesis adhesion stage was revealed in vitro. Conclusion. Hyperactive response of leukocytes and macrophages can be the cause of recurrent ulcer bleedings.